ANALISIS PERBEDAAN HARGA, VOLUME PERDAGANGAN, DAN RETURN SAHAM SEBELUM DAN SESUDAH INFORMASI AKUISISI PADA PT. XL AXIATA Tbk.. dan PT. AGUNG PODOMORO LAND Tbk. - Tasa Ushuaia; Bulan Prabawani (Jurnal Ilmu Administrasi Bisnis, 2016)
Economic development requires company to work better and be able to survive from an intense competition between companies. In modern era, telecommunication and property industries are the most developed industry. In maintaining the continuity of business, there are several strategies that can be undertaken by company, one of which is the incorporation of a business entity such as an acquisition.                The purpose of this research is to find differentiation among stock price, stock trading volume and stock return before and after acquisition on the telecommunication and property industry, acquisition of PT. XL Axiata Tbk. with Axis Telekom Indonesia and acquisition between PT. Agung Podomoro Land Tbk. and PT. Graha Cipta Karisma.                The results show a significant difference to stock price before and after acquisition information of PT. XL Axiata Tbk. and PT. Agung Podomoro Land Tbk., but no significant difference on trading volume and stock return (indicated by abnormal return to see information content from that event). Based on these results it can be concluded that investor opinion on the acquisition information is normal so the trading volume and stock return are not change significantly. The significant difference of stock price may be due to investors's views about the acquisition and its accordance with the theory saying that acquisition can improve companies performance.